Receptor tipo quinase de tomate: caracterização molecular e implicações nas infecções virais - Costa, Alessandra Tenório [UNESP] (2014)
The exposure of plants to various biotic and abiotic stresses interferes with the expression patterns of different host genes. Studies on differential gene expression in tomato plants infected with Pepper yellow mosaic virus (PepYMV) revealed the repression of a gene encoding a leucine-rich repeat receptor-like kinase (LRR-RLK). However, this receptor didn’t figure among the receptors induced in tomato during the infection of a viral species belonging to the Tospovirus genus, suggesting a differential behavior of this gene in response to other virus species. LRR-RLKs constitute a diverse group of proteins anchored in the plasma membrane allowing the cell to recognize and respond to the extracellular environment, being a component of the signal transduction pathway. This study aimed to perform a molecular and functional characterization of the gene encoding such a LRR-RLK from tomato (Solanum lycopersicum) (recently nominated SlSOBIR1) infected by PepYMV and Tomato chlorotic spot virus (TCSV), Tospovirus genus, in order to reveal a possible implication of this receptor in triggering defense responses during infection by these two viral species. Molecular characterization of SlSOBIR1 was acquired through the determination of its expression profile in response to PepYMV and TCSV infection, respectivelly, and to mechanical wounding employing real-time PCR. In parallel, SlSOBIR1 expression levels on different tomato organs/tissues were determined and protein subcellular localization investigated, and a phylogenetic tree was constructed. In functional studies, the effect of SlSOBIR1 overexpression in tobacco plants infected with each virus species was observed. Furthermore, we investigated the expression of previously selected defense genes and determined reactive oxygen species accumulation in SlSOBIR1-overexpressors. The results revealed that the expression of SlSOBIR1 is modulated differently in tomato plants infected PepYMV (repression) ...